Correlation between compounding sequence and the properties of glass fiber‐Reinforced nylon‐6, 6 composite. Issue 1 (18th May 2018) - Mun, Hyung Jin; Cha, Sang Hoon; Choi, Pil Sung; Kim, Jae Ik; Ryu, Sung Hun
Abstract : The effects of the compounding sequence and addition of maleic anhydride grafted polypropylene (PP ‐g‐ MAH) as a sizing agent on the properties of glass fiber (GF)/nylon‐6, 6 composite were investigated. Mechanical properties of tensile, impact, and flexural strength were measured. The fractured surface was analyzed to compare the variation of interfacial characteristics by different compounding sequences and addition of a sizing agent. It was found that mechanical and rheological properties of a composite are strongly affected by the compounding sequence and the addition of a sizing agent. In general, the addition of PP ‐g‐ MAH results in lowering the mechanical properties compared to GF/nylon‐6, 6, while proper compounding sequence results in improved mechanical properties. Lowering melt viscosity of composites is achieved by addition of sizing agent and varied depending on the compounding sequence. POLYM. ENG. SCI., 59:155–161, 2019. © 2018 Society of Plastics Engineers